Gold in education and elite sport: A Flemish perspective on the competences of elite pupil-athletes and student-athletes - De Brandt, K.; Wylleman, P.; Defruyt, S.; Taelman, K. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction. Elite athletes face challenges in different domains (i.e. athletic, psychological, social, academic and financial) during their dual `elite sport and study` career (DC)°. To cope with these challenges, athletes require a set of competences in order to optimize their preparation for, and development throughout their DC°°. Aim. While past research generally used a qualitative approach to identify the competences required for a successful DC°°, this study used a quantitative approach to identify the competences (i.e. skills, attitudes, knowledge, experiences) athletes require to optimally prepare, manage and finalize their `education and elite sport` pathway. Method. The online survey of the Erasmus+ Sport project `Gold in Education and Elite Sport`, which focused on i) the importance and possession of a predefined list of 38 DC competences on a 5-point scale, and ii) the importance and use of these competences in 7 specific challenging DC situations (`DC scenarios`), was presented to 891 Flemish 15-25 year-old athletes combining elite sport and study. SPSS was used for descriptive and comparative analyses, and MPlus was used for Exploratory Structural Equation Modelling (ESEM). Results. 524 athletes (59%) responded to the survey (mean age 17.6 ± 2.3 years; 61% male athletes vs. 39% female athletes; 74% pupils vs. 26% students). While all competence items were rated as important to very important (4.3 ± .70), scores for possession were significantly lower (3.6 ± .87; p<.001) with the largest difference between importance and possession found in management of mind and emotion (e.g. coping with stress, using setbacks as positive stimulus) and life management competences (e.g. efficient use of time; conscientious pro-active planning). On average, student-athletes experienced more scenarios than pupil-athletes (respectively 4.3 and 3.4; p<.001). For each of the 7 scenarios, a set of transferable competences (useable across multiple scenarios) and specific competences (needed in a specific challenging situation) was defined. Further detailed results (i.e. scenarios, inter-individual differences and the ESEM results) will be presented. Discussion. A set of competences and scenarios relevant for a DC was identified. The use of `scenarios` guaranteed contextspecificity and the identification of transferable and specific competences. DC-support providers should be aware of these transferable and spcific competences in order to proactively assist and empower athletes during their DC pathway.